(untitled) (CONTINUIDAD Y DISCONTINUIDAD EN EL ESPACIO IBEROAMERICANO, 2026)
If we think of Aunt Julia and the Scriptwriter, The Storyteller, or In Praise of the Stepmother, to name just a few titles, at first reading it seems that we are facing two novels in one, and the deconstruction of a classical chronology and structure is noticeable when moving from one chapter to another. However, as we enter the core of the works and pay close attention, we find all kinds of clues or signs that the author offers us to piece together the literary puzzle and thus understand the novels in their entirety. This is how we discover that the even chapters of Aunt Julia and the Scriptwriter represent the radio soap operas that Pedro Camacho creates, and the effects of his madness in real life—meaning in the odd chapters—also affect the stories presented in the even chapters. Or that the descriptions of the paintings in In Praise of the Stepmother are in fact the erotic fantasies of Don Rigoberto and Lucrecia.